Environmental Reviews and Case Studies: Unique Landfill Restoration Designs Increase Opportunities to Create Urban Open Space. (1st June 2016) - Hoefer, Wolfram; Gallagher, Frank; Hyslop, Theresa; Wibbelt, Tyler J.; Ravit, Beth
Abstract : The majority of humans now live in cities where access to usable open space is often limited, causing a reexamination of current practices and values related to reuse of available urban lands. Closed landfills offer an unprecedented opportunity to convert large underutilized land into usable urban open space, as well as habitat for multiple species. However, existing landfill regulations and closure practices do not allow optimal ecological restoration designs for these underutilized properties to be realized, because current regulations focus on methods that protect required caps and prevent water infiltration. Through the exploration of two design case studies, the authors illustrate the opportunities to increase habitat diversity on closed landfills and to more closely approximate a natural topographic/vegetation interaction. Although initially a more costly restoration, unique restoration design elements enhance both long-term environmental and socio-economic values associated with the reuse of closed urban landfills, which are currently underutilized.